RELATIONSHIP BETWEEN FAMILY SUPPORT AND FUNCTIONAL INDEPENDENCE IN POST-STROKE ELDERLY PATIENTS - Nurjannah; Urista Wulandari (STIKES Estu Utomo, 2026)
Background: Stroke is one of the leading causes of disability in the elderly, often resulting in limitations in performing activities of daily living (ADL). Family support plays a crucial role in the recovery process of post-stroke patients. Purpose: This study aimed to determine the relationship between family support and the ability to perform activities of daily living among elderly post-stroke patients at Siti Fatimah General Hospital Palembang in 2025. Methods: This research employed a quantitative correlational analytic design with a cross-sectional approach. The study population consisted of 85 elderly post-stroke patients in the physiotherapy unit, with a sample of 33 respondents selected based on inclusion and exclusion criteria. Data collection instruments included the Caregiver Reaction Assessment (CRA) to measure family support and the Barthel Index to assess ADL ability. Data were analyzed using the Chi-Square test with SPSS version 26. Results: The findings showed that most respondents had a high level of family support (25 respondents, 75.7%) and moderate support (8 respondents, 24.3%). Regarding ADL, the majority of respondents were in the moderate dependency category (15 respondents, 45.5%). The Chi-Square test revealed a p-value = 0.002 (p < 0.05), indicating a significant relationship between family support and ADL ability among elderly post-stroke patients. Conclusion: There is a significant relationship between family support and the ability to perform activities of daily living in elderly post-stroke patients. Higher family support plays a key role in enhancing patients’ independence in meeting their ADL needs.